1989
DOI: 10.1136/hrt.61.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic findings in male veteran endurance athletes.

Abstract: SUMMARY Twenty male veteran endurance runners and 20 controls underwent resting, exercise, and ambulatory electrocardiography. Four athletes and three controls satisfied voltage criteria for left ventricular hypertrophy. The PR interval was longer in the athletes and they had longer mean (SD) treadmill exercise times (19 (4) v 16 (2) min) than the controls. Four athletes but no controls had > 2 mm downsloping ST segment depression during exercise. During 48 hour ambulatory electrocardiography the athletes had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 28 publications
2
56
1
Order By: Relevance
“…The prevalence was low and it was not higher in top athletes than athletic stu dents. Increased prevalence of AV block II in athletes compared to controls has been found by other authors [10,19,20,22,25,26]. Most blocks occurred during the night, and Viitasalo et al [10] demonstrated that blocks had the highest prevalence during sleep-related rapid changes in heart rate probably induced by changes in the autonomic nervous tone.…”
Section: Sinoatrial and Atrioventricular Blocksmentioning
confidence: 67%
See 3 more Smart Citations
“…The prevalence was low and it was not higher in top athletes than athletic stu dents. Increased prevalence of AV block II in athletes compared to controls has been found by other authors [10,19,20,22,25,26]. Most blocks occurred during the night, and Viitasalo et al [10] demonstrated that blocks had the highest prevalence during sleep-related rapid changes in heart rate probably induced by changes in the autonomic nervous tone.…”
Section: Sinoatrial and Atrioventricular Blocksmentioning
confidence: 67%
“…(tables 1, 3) The number of VPB was low in all groups and no consistent differences could be found. The prevalence of VPBs has been reported in matched trained and untrained groups [12,19,21,22] of varying ages and range between 17 and 90%, but the differences are not con sistent and not statistically significant. While Palatini and Sperti [12] suggested an in creased prevalence of complex ventricular ar rhythmias in athletes based on a prolongation of the QT time, Freggiaro et al [21] found a low prevalence which is supported by the results of the present study.…”
Section: Heart Ratementioning
confidence: 96%
See 2 more Smart Citations
“…Resting sinus bradycardia, as defined by a heart rate <60 beats/min, is almost universal in athletes, depending on the type of sport and the level of training/competition 18 19 20. Escape junctional beats or rhythm may be recorded in athletes with more severe bradycardia and result in functional AV dissociation.…”
Section: Common and Training-related Ecg Changesmentioning
confidence: 99%